Pleiotropic Effects of Glitazones: A Double Edge Sword? - Salomone, Salvatore (Frontiers in Pharmacology, 2011)
Glitazones (thiazolidinediones) are drugs used for diabetes mellitus type 2. By binding to Peroxisome Proliferator-Activated Receptor γ (PPARγ) they modulate transcription of genes of carbohydrate and lipid metabolism. Through PPARγ stimulation, however, glitazones also affect other genes, encompassing inflammation, cell growth and differentiation, angiogenesis, which broads their therapeutic potential. The gene expression profile induced by each glitazone shows peculiarities, which may affect its benefit/risk balance; indeed, troglitazone and rosiglitazone have been associated with liver failure and coronary disease, respectively; whether or not these severe adverse effects are solely related to PPARγ remains yet unclear, since glitazones exert also PPARγ-independent effects. Glitazone chemistry serves as scaffold for synthesizing new compounds with PPARγ-independent pharmacological properties and we report here a preliminary observation of inhibition of vasoconstriction by troglitazone in isolated vessels, an effect that appears fast, reversible and PPARγ-independent. Pleiotropic effects of glitazones need specific attention in terms of drug safety, but also provide basis for drug development and novel experimental therapeutics